Moderation of profitability against determinants company value - Kadang, Juliana; Nurdin, Djayani; Kasim, Yunus; Moh, Husnah (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2023)
Banks in carrying out the intermediation function require additional capital. Therefore, part of the bank's ownership is sold to the public in the form of shares and debt securities. Firm value is one of the indicators for investors in assessing the performance of a company. The aims of this study are: 1) To determine the factors that influence the value of Indonesian banking companies. These factors are capital structure, efficiency and size of the bank. 2) To find out that profitability moderates the value of Indonesian banking companies. This research uses quantitative verification research. The research analysis technique with moderate variables uses the Moderated Regression Analysis (MRA) model. Using secondary data from the financial statements of each bank. The financial reports are downloaded through the Indonesia Stock Exchange (IDX) website. Processing data using the e-Views 11 application. The results of this study show that the capital structure and the size of the bank have a significant positive impact on corporate value. If a bank is inefficient, it will not have a significant impact on corporate value. Profitability as a mitigation variable cannot amplify the impact of capital structure, efficiency, or bank size on corporate value.